Influential Article Review - Various Viewpoints on Crime and Criminality: A Look at Perspectives From the Periphery - Paul, Jameson; Villegas, Talha; Lim, Aahil (Journal of Leadership, Accountability and Ethics, 2021)
This paper examines criminality. We present insights from a highly influential paper. Here are the highlights from this paper: The study presents a case for expanding discussions about crime to include ideological variances, circumstances and societal contexts. A content analysis approach was used to interpret civilian interviews reflecting the problematic acceptance of crime as an understood construct and to highlight the need for recognition of interpretative diversities. The study analyses civilians’ perspectives that are critical to an understanding of how they view crime and outlines the possible impact of such understandings on their relations with police officers. The article presents a case for the consideration of alternative understandings of crime, which contradict state delineation, and for reflection on the potential impact of these interpretations on enhancing the interface between police officers and civilians. For our overseas readers, we then present the insights from this paper in Spanish, French, Portuguese, and German.